Characterization and anti-tumor activity of saponin-rich fractions of South Korean sea cucumbers (Apostichopus japonicus) - Dai, Yu-Lin (J Food Sci Technol, 2020)
In this study, the saponin-rich fractions of five individual (two Red and three Black) sea cucumbers (Apostichopus japonicus) in South Korea were investigated for their antiproliferative effect against HL-60, B16F10, MCF-7, and Hep3B tumor cell lines. The red sea cucumber saponin-rich fraction (SSC) from Jeju Island (JRe) decreased the growth of HL-60 with an IC(50) value of 23.55 ± 3.40 μg/mL, which represented the strongest anticancer activity among the extracts. Further, SSC downregulated B-cell lymphoma extra-large (Bcl-xL), while upregulating, to different degrees, Bcl-2-associated X protein (Bax), caspase-9, caspase-3, PARP cleavage, and apoptotic bodies in cancer cells. Evidence for SSC inducing apoptosis via the mitochondria-mediated pathway was found. The contents of SSCs were determined using ultra high-performance liquid chromatography coupled with a quadrupole orbitrap mass spectrometry to comparatively evaluate the regional influence. In West Sea, the total SSC content of A. japonicus was 15.5 mg/g, representing the highest content, while A. japonicus in the South Sea yielded the lowest content at 8 mg/g. The major saponin constituent in SSC was identified as Holotoxin A(1), which may the anti-tumor compound in A. japonicus.